TWO MEDICALLY IMPORTANT BEETLES OF FARS PROVINCE (IRAN): PAEDERUS SPP. (COL: STAPHYLINIDAE) & ITS LINEAR DERMATITLS - MR. Nikbakhtzadeh; S. Tirgari (Tehran University of Medical Sciences, 1999)
The present study was performed during spring, summer and fall of 1997 in the central and western parts of Fars province, Iran, led to identification of Paederus ilsae bernhauer and Paederus iliensis coiffait (Col: staphylinidae). This is the first original report of the latter species from Iran. The adults have 5 months activity in average, begin lately in April and then continue until early September; soon afterwards they endure the inclement climate. This over wintering period takes 6-8 month long according to the region. P.ilsae has two annual generations in most regions; the population arising from the first one is more significant. According to clinical records and reports, it has been noticed that the yearly epidemics of linear dermatitis coincide when Paederus population reach its peaks. Paederus ilsae is dominant species and also principal agent of linear dermatitis.